Taiwan Society of Colon and Rectal Surgeons Consensus on mCRC Treatment - Chen, Hong-Hwa; Ke, Tao-Wei; Huang, Ching-Wen; Jiang, Jeng-Kae; Chen, Chou-Chen; Hsieh, Yao-Yu; Teng, Hao-Wei; Lin, Bo-Wen; Liang, Yi-Hsin; Su, Yu-Li; Hsu, Hung-Chih; Kuan, Feng-Che; et al. (Frontiers in Oncology, 2021)
Therapeutic options for metastatic CRC (mCRC) have changed significantly in recent years, greatly increasing the complexity of therapeutic decision making. Although oncology guidelines have helped improve the care process, guidelines may also limit the flexibility to individualize in-clinic decision making. This consensus paper addresses specific gaps in the current international guidelines to assist Taiwanese colon and rectal experts make specific therapeutic choices. Over three years and three meetings with selected experts on “real- world” Taiwanese practice patterns for mCRC, consensus was achieved. The experts also discussed specific questions during in-depth one-on-one consultation. Outcomes of the discussion were then correlated with published evidence by an independent medical writer. The final consensus includes clinically implementable recommendations to provide guidance in treating Taiwanese mCRC patients. The consensus includes criteria for defining fit and unfit intensive treatment patients, treatment goals, treatment considerations of molecular profiles, treatment consideration and optimal treatment choices between different patient archetypes, including optimal treatment options based on RAS, BRAF and microsatellite instability (MSI) status. This consensus paper is the second in the Taiwan Society of Colon and Rectal Surgeons (TSCRS) Consensus series to address unmet gaps in guideline recommendations in lieu of Taiwanese mCRC management. Meticulous discussions with experts, the multidisciplinary nature of the working group and the final drafting of the consensus by independent medical professionals have contributed to the strong scientific value of this consensus.